Acute psilocybin increased cortical activities in rats - Liu, Junhong; Wang, Yuanyuan; Xia, Ke; Wu, Jinfeng; Zheng, Danhao; Cai, Aoling; Yan, Haitao; Su, Ruibin (Frontiers in Neuroscience, 2023)
Psilocybin, a naturally occurring hallucinogenic component of magic mushrooms, shows great therapeutic potential for depression in humans. But the underlying mechanisms have not been fully understood. Blood-oxygenation level dependent (BOLD) functional magnetic resonance imaging (fMRI) is a useful tool in many preclinical and clinical trials to investigate psilocybin-induced changes of brain activity and functional connectivity (FC) for its noninvasive nature and widespread availability. However, fMRI effects of psilocybin on rats have not been carefully investigated. This study aimed to explore how psilocybin affects resting-state brain activity and FC, by a combination of the BOLD fMRI and immunofluorescence (IF) of EGR1, an immediate early gene (IEG) closely related to depressive symptoms. Ten minutes after psilocybin hydrochloride injection (2.0 mg / kg, i.p.), positive brain activities were observed in the frontal, temporal and parietal cortex (including cingulate cortex and retrosplenial cortex), hippocampus and striatum. And region-of-interest (ROI) -wise FC analysis matrix suggested increased interconnectivity of several regions, such as cingulate cortex, dorsal striatum, prelimbic and limbic regions, with multiple other regions. Further seed-based analysis revealed increased FC of cingulate cortex with cortical and striatal areas. Consistently, acute psilocybin increased the EGR1 level throughout brain, indicating a consistent activation throughout cortex, hippocampus and striatum, amygdala, and hypothalamus. Both BOLD fMRI and IF EGR1 results suggested that psilocybin-induced hyperactive state of rat is congruent to that of human, which may be responsible for its pharmacological effects.